Team : getting things done with others - Allen, David, 1945 December 28-; Lamont, Edward (Viking, 2024)
"A groundbreaking book about how to harness the power of collaboration and work most effectively in groups-coauthored by Getting Things Done's David Allen When Getting Things Done was published in 2001, it was a game changer. By revealing the principles of healthy high performance at an individual level, it transformed the experience of work and leisure for millions. Twenty years later, it has become clear that the best way to build on that success is at the team level, and one of the most frequently asked questions by dedicated GTD users is how to get an entire team onboard. By building on the effectiveness of what GTD does for individuals, Team will offer a better way of working in an organization, while simultaneously nourishing a culture that allows individuals' skills to flourish. Using case studies from some of the world's largest and most successful companies, Team shows how leaders have employed the principles of team productivity to improve communication, enable effective execution, and reduce stress on team members. These principles are increasingly important in the post-pandemic workplace, where the very nature of how people work together has changed so dramatically. Team is the most significant addition to the GTD canon since the original, and in offering a roadmap for building a culture of healthy high performance, will be welcomed by readers working in any sized group or organization"--